Relationship between sociodemographic, anthropometric and biochemical characteristics and degree of peripheral arterial disease - Radak Đorđe; Marinković Jelena; Đurišić Nebojša; Jorga Jagoda; Maksimović Miloš; Vlajinac Hristina (Srpski Arhiv za Celokupno Lekarstvo, 2010)
Introduction. Peripheral arterial disease (PAD) is a severe atherosclerotic condition. The relationship between various risk factors and severity of PAD, measured by Ankle Brachial Index (ABI), has been the subject of a relatively small number of studies. Objective. The aim of the present study was to investigate whether there was any relationship between severity of PAD, expressed as ABI, and anthropometric, clinical and biochemical characteristics of patients, including inflammatory markers. Methods. The cross-sectional study, involving 388 consecutive patients with verified PAD, was performed at the Dedinje Vascular Surgery Clinic in Belgrade. The diagnosis of PAD was defined by Doppler sonography as ABI<0.9, and by symptoms. Data on cardiovascular risk factors, anthropometric parameters, clinical and biochemical characteristics were collected for all participants. In the analysis, χ2 test, t-test and multivariate logistic regressions were used. Results. According to the results of multivariate analysis (the model of which included age, percentage of body fat, average value of uric acid, high sensitivity C-reactive protein - hsCRP ≥3 mg/L, fibrinogen ≥4 g/L, Baecke index of physical activity at work and Baecke index of leisure-time physical activity), the patients with more severe form of peripheral arterial disease (ABI≤0.40) had more frequently increased high sensitivity C-reactive protein (p=0.002), lower Baecke index of physical activity at work (p=0.050) and lower Baecke index of leisure-time physical activity (p=0.024). Average value of body fat was significantly higher in the patients with a less severe form of disease (p=0.006). Conclusion. According to the results obtained, the increased values of hsCRP and physical inactivity are associated with a more severe form of PAD (ABI≤0.40).